Coffee and Tea with APB Seremban / Evelyn Sharminnie S.Vasuthavan, Afni Anida Adnan and PM Khas Dr. Angeline Ranjethamoney Vijayarajoo - S.Vasuthavan, Evelyn Sharminnie; Adnan, Afni Anida; Vijayarajoo, PM Khas Dr. Angeline Ranjethamoney (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2022)
In keeping with its mission to enhance language scholarship and excellence, The Academy of Language Studies, Seremban campus organized a 3 series webinar which was held on the 21st January, 28th January and 4th February, 2022 respectively. The purpose of these webinars was to showcase The Academy of Language Skills by introducing the services offered and the skills and expertise available. Besides that, these webinars were also to highlight the third languages that are offered such as the Arabic and Mandarin languages. These webinars were also carried out to expose the academic and administrative staff of UITMNS, Seremban Campus staff, to the correct pronunciation and usage of words in the English Language, Arabic and Mandarin languages. The focus was on the commonly mispronounced and misused words and phrases in daily conversations and conversely, to increase the understanding of different cultures among Malaysians.